Hearing aid use on audit temporal temporal processing in conductive hearing loss - ÇİPRUT, AYŞE AYÇA; AKDENİZ, ESRA (My University, 2022)
Objective: The chronicity of the problem of conductive pathologies, the lack of improvement with treatment, and the progression of hearing loss are seen as important criteria for using hearing aids. The aim of this study was to investigate the effect of conductive pathologies and the use of hearing aids on temporal processing.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; KULAK BURUN BOĞAZ; Klinik Tıp; Klinik Tıp (MED); OTORHINOLARYNGOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Konuşma ve İşitme; Speech and Hearing; Otorhinolaryngology; Gaps in noise; temporal auditory processing; conductive pathologies; hearing aid use; COCHLEAR NUCLEUS; BRAIN-STEM; DEPRIVATION; PLASTICITY; TINNITUS